Cologne marks or French livres, or financing and currency conversions during the 4th Crusade, in the light of the agreement of April 1201 and the chronicles of Geoffroy de Villehardouin and Robert of Clari - Pentek, Zdzisław (Balcanica Posnaniensia. Acta et studia, 2020)
The paper focuses on the financing of the 4th crusade and the agreement of April 1201 among the future leaders of the crusade with Venice. I discuss the problem of the currency conversion of Cologne marks and French livres in the chronicles of Geoffroy de Villehardouin and Robert of Clari. It has been established that the sum of 50 000 livres paid by the crusaders and mentioned by Robert Clari is not real. Actually, it was the sum of 50 000 Cologne marks, which had a much lower value. If the sum were 50 000 French livres, it would cover the cost the crusaders committed to bear, because 50 000 livres equaled at the time 20 450 kilograms of silver, and the whole sum the crusaders were obliged to pay was 85 000 Cologne marks or 19890 kilograms of silver. Yet, it is known that having paid the 50 000 livres and adding a thousand collected by the soldiers, there remained a debt of 34 000 Cologne marks, which the crusaders had to work off in Venetian service. The organizers of the 4th crusade overestimated the number of its future participants and they concluded an agreement with Venice exaggerating the future development. They ordered the construction of the fleet and provisions for one year for too many expected crusade participants. In result, those who turned up for the crusade were not able to cover its huge costs.